Multiple Recognition-Based Sensor for Pesticide Residues - Li, Jie; Chen, Keren; Zhu, Longjiao; Li, Xiangyang; Li, Changmo; Chang, Qiaoying; Xu, Wentao (Frontiers in Chemistry, 2022)
The use of pesticides is gradually increasing to improve the yield and quality of crops. However, excessive pesticide use has led to a dramatic pollution increase in the environment and agricultural products, posing severe human health risks. Therefore, rapid, sensitive pesticide detection is essential. Various pesticides detection methods and products have been developed in recent years. This brief review summarized the point-of-care testing (POCT) detection of pesticides based on multiple recognition, including protein-, aptamer-, nanomaterial-, and macrocycle-based recognition. The review aimed to address the growing demands for regulating and destroying pesticides or other adverse agriculture-related applications in the real world.